Tetrahedral DNA conjugates from pentaerythritol-based polyazides. Issue 19 (12th May 2016) - Ponomarenko, Anna I.; Brylev, Vladimir A.; Sapozhnikova, Ksenia A.; Ustinov, Alexey V.; Prokhorenko, Igor A.; Zatsepin, Timofei S.; Korshun, Vladimir A.
Abstract: Branching points in DNA nanostructures are usually 3- or 4-way junctions maintained by Watson-Crick non-covalent interactions. However, covalently bound DNA stars could improve the diversity, strength and integrity of DNA nanoscale constructions. We report here the convenient synthesis of 3- and 4-fold pentaerythritol-based azides and their use for the assembly of branched conjugates containing the same or different oligonucleotides (ODNs) and/or fluorescent dyes by stoichiometry controlled copper (I) catalyzed azide alkyne cycloaddition (CuAAC) functionalization. Graphical abstract: